The use of immunoenzymatic method for detection of antibodies against zoonotic diseases in Czech soldiers returning from Afghanistan - Straková, Petra; Rudolf, Ivo; Pavliš, Oto; Hubálek, Zdeněk (Vojenské zdravotnické listy, 2014)
In this work, we focused on detection of IgG antibodies in the blood sera from Czech soldiers returning from Afghanistan against selected zoonotic diseases by commercially available ELISA kits. Samples were tested for the presence of antibodies against Brucella abortus, Coxiella burnetii, Leptospira spp., complex of Rickettsia conorii, Leishmania infantum, hantaviruses and hepatitis E virus. Except for L. infantum (all persons were negative), we found following seroreactivity rate: 10 % in B. abortus, 11 % in C. burnetii, 20 % in Leptospira spp., 10 % in R. conorii and 4 % in both hepatitis E virus and hantaviruses.
Keywords: Enzyme-Linked Immunosorbent Assay; Zoonoses; Afghánistán; zoonózy; ozbrojené síly; imunoglobulin G; Hepevirus; Leishmania infantum; Coxiella burnetii; lidé; Rickettsia conorii; Afghanistan; Antibodies; Military Personnel; Brucella abortus; Immunoglobulin G; ELISA; Czech Republic; Česká republika; Leptospira; Orthohantavirus; protilátky; Hantavirus; Humans